Processes affecting the distribution of PCBs in the Southern Ocean - Pizzini, Sarah; Scalabrin, Elisa; Radaelli, Marta; Piazza, Rossano; Capodaglio, Gabriele (Università degli Studi di Napoli "Parthenope", 2023)
Polychlorinated biphenyls (PCBs) are a broad class of globally distributed persistent pollutants that differ in their degree of chlorination and, thereby, in their volatility and are subject to long-range atmospheric transport (LRAT). Although their industrial production was discontinued in the early nineties, some PCB congeners are still released into the environment as unintentional by-products of dye manufacturing and other chemical productions. Among them, 3,3’-dichlorobiphenyl (PCB-11) has been detected at concentrations often higher than those of the other technical congeners (i.e. legacy Aroclor PCBs) in almost all the environmental compartments, even in polar areas (Choi et al., 2008). It is known that the atmosphere plays a key role in transport and distribution of persistent organic pollutants (POPs) towards polar areas, through successive phases of volatilization and deposition that occur at the air/water interface. The low temperatures of the polar areas promote this partition between the atmosphere and the seawater surface via the cold trapping mechanism (Wania and MacKay, 1996). However, this process is reversible, so the partition of POPs moves in one direction or in the opposite one depending on the volatility of the molecules involved, their relative concentration in air and water, and changes in temperature (Galbán-Malagón et al., 2013). As the surface water temperature decreases, lighter congeners, more prone to volatilization, tend instead to settle in the water surface layers. Indeed, in the Southern Ocean, where the temperature of surface water is reduced to values close to that of the air, a particularly high concentration of PCB-11 compared to that of other less volatile PCB congeners have been reported (Choi et al., 2008; Pizzini et al., 2017). Instead, PCBs with a higher degree of chlorination are less prone to volatilization in temperate areas and, consequently, they would be preferentially transferred to the Southern Ocean through Modified Circumpolar Deep waters (Fuoco et al., 2009) ...